The relevance of Vygotsky's constructivism learning theory with the differentiated learning primary schools - Wibowo, Sigit; Wangid, Muhammad Nur; Firdaus, Fery Muhamad (Journal of Education and Learning (EduLearn), 2025)
The purpose of this study is to analyze in depth the relevance of Vygotsky's constructivism learning theory in differentiated learning in elementary schools. Differentiated learning is an effort to adapt the learning process in the classroom to meet the learning needs of each individual. This adjustment is made by considering the interests, learning profiles, and readiness of students to improve learning outcomes. With this adjustment, students can learn according to their respective abilities and find understanding from their own experiences. On the other hand, constructivist learning theory states that learning is a process in which students can build their knowledge. One of the constructivists learning theories was proposed by Vygotsky, known as social constructivism. Vygotsky's constructivism emphasizes the interaction of interpersonal (social), cultural-historical, and individual factors as the key to human development. The constructivist theory has relevance to differentiated learning in terms of meaningful learning and student activity. Differentiated learning applies constructivist theory in learning by considering the individual characteristics of students. In addition, the concept of the zone of proximal development (ZPD) and scaffolding are highly relevant in differentiated learning that accommodates the full potential of students and considers the individual abilities of students.